1946
DOI: 10.5254/1.3543254
|View full text |Cite
|
Sign up to set email alerts
|

Tackiness of GR-S and Other Elastomers

Abstract: The analysis of tackiness shows that it is a complex property which depends on a balance between a large number of different factors, including the geometry of the sample as well as the surface forces and the visco-elastic properties of the material itself. The quantitative measurements of the effect of the rate of removal on the apparent tackiness of pressure-sensitive adhesive tapes show that significant differences are found at very slow removal rates (105 seconds per cm.) which do not show up at much highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1947
1947
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Meanwhile, other literatures have also reported that addition of carbon black to SBR and EPDM lowers the tack strength as compared to that of the gum elastomers. 4,10,11,25,26 On the contrary, adding nanoclay content above 8 phr, sufficiently improved the green strength of the specimen without the material losing its original interdiffusion or contact flow properties fully. According to Kumar et al, 8 it is well-known that the addition of reinforcing fillers will increase the green strength of synthetic elastomers and can reduce the contact flow and extent of diffusing rubber molecules at the tack junction.…”
Section: Effect Of Nanoclay On the Tack Strength Of Biir-clay Nanocommentioning
confidence: 99%
See 3 more Smart Citations
“…Meanwhile, other literatures have also reported that addition of carbon black to SBR and EPDM lowers the tack strength as compared to that of the gum elastomers. 4,10,11,25,26 On the contrary, adding nanoclay content above 8 phr, sufficiently improved the green strength of the specimen without the material losing its original interdiffusion or contact flow properties fully. According to Kumar et al, 8 it is well-known that the addition of reinforcing fillers will increase the green strength of synthetic elastomers and can reduce the contact flow and extent of diffusing rubber molecules at the tack junction.…”
Section: Effect Of Nanoclay On the Tack Strength Of Biir-clay Nanocommentioning
confidence: 99%
“…6,8 It has also been reported that the addition of reinforcing fillers like carbon black can influence the tack strength of elastomers. [9][10][11][12][13] For instance, addition of 40 phr of carbon black to natural rubber (NR) resulted in a significant increase in the tack strength of NR. 9 The increase in the tack strength has been attributed to an increase in cohesive strength due to filler reinforcement.…”
Section: ⅰ Introductionmentioning
confidence: 99%
See 2 more Smart Citations